Deformation and Failure Law of Roadway along Goaf and Reserve Width of Section Coal Pillar. (7th July 2022) - Chen, Yunsheng; Sun, Jian; Pang, Di; Zhang, Ruofei
Abstract : It was a non-negligible problem in the reserve of section coal pillar in coal mining. Reasonable section coal pillar width and support parameters can not only ensure the stability of surrounding rock of roadway but also produce more coal resources and save support cost. In this paper, the mining of 9106 workface of Linfen Tianyu Hengsheng Coal Industry of Wanbei Coal Power Group was taken as the research engineering background. FLAC 3D numerical simulation software was used to simulate and analyze the laws of deformation failure of 6 m, 7 m, 8 m, 9 m, and 10 m coal pillars and surrounding rock of roadway along goaf without support conditions during the mining of 9106 workface. On this basis, the deformation failure law of 7 m and 8 m coal pillars and surrounding rock of roadway along goaf under different supporting conditions (bolt and cable with different row spacing) were further simulated and analyzed. The results showed that when 7 m coal pillars were reserved in 9106 roadway along goaf, the optimal bolt row spacing was 800 mm. When 8 m coal pillars were reserved, the bolt row spacing was preferred to be 900 mm. At this time, the width of coal pillar and support parameters can ensure the stability of roadway surrounding rock during the mining process of 9106 workface and can produce more coal resources and save support cost.